International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The fourth volume of the proceedings of the International Conference on Transportation and Development 2022. This collection contains 30 peer-reviewed papers on transportation planning and workforce development. Topics include: planning and visualization of transportation infrastructure; modeling and predicting travel behavior; pedestrians and bicycles; travel patterns and the pandemic; and workplace occupational health hazards.
Keywords: Transportation -- Planning -- Congresses.; Traffic patterns -- Congresses.; Traffic monitoring -- Congresses.; Construction workers -- Congresses.; elektronické knihy; electronic books